A Comparative Analysis of Kocher’s Method And Scapular Manipulation In Reducing Shoulder Dislocation: A Quasi-Experimental Study - Wahab, Abdul; Ijaz, Osama; Riaz, Saad; Farhan, Muhammad; Shehzad, Faizan (Journal of Rawalpindi Medical College, 2026)
Objective: Anterior shoulder dislocation is a common orthopedic emergency requiring prompt reduction. This study aimed to compare the mean reduction times of the Scapular Manipulation Technique (SMT) and Kocher’s Method using a quasi-experimental design. Methods: This quasi-experimental study was conducted in the Department of Orthopedics, Rawalpindi Teaching Hospital, from September 2021 to March 2022. Patients aged 16–60 years presenting with acute anterior shoulder dislocation within 24 hours of injury were included. Participants were allocated alternately to either SMT without sedation (Group A) or Kocher’s Method under intravenous sedation and analgesia (Group B). Reduction time was recorded from initiation of the maneuver to clinical confirmation. Data were analyzed using SPSS version 22. Independent t-tests were used, and p < 0.05 was considered statistically significant. Results: A total of 60 patients were included, with 30 in each group. Mean reduction time was significantly shorter in Group A (2.7 ± 0.46 minutes) compared to Group B (4.13 ± 0.6 minutes), p = 0.000. Both techniques achieved a 100% success rate, and no complications were observed. Conclusion: Both SMT and Kocher’s Method are effective for reducing anterior shoulder dislocations. However, SMT was associated with significantly shorter reduction times and avoids the need for sedation, making it a practical option in emergency and resource-limited settings. Keywords: Shoulder Dislocation; Scapular Manipulation; Kocher’s Method; Quasi-Experimental Study; Reduction Techniques.